(untitled) (Development Service Industry Management, 2025)
The concepts of development and enterprise development are examined. Existing viewpoints on the essence of enterprise development are shown. Feasibility of formalizing enterprise development in the form of specific evaluations or other generalizations of its progress is demonstrated. Existing approaches to assessing enterprise development are outlined. Due to a synthetic nature of enterprise development assessments in most evaluation approaches, the need for further research on the formalization of enterprise development, including usage of scenario-based tools, is substantiated. Various types of enterprise development are highlighted, including organizational, economic, socio-economic, innovative, and sustainable development. The concept of enterprise development is visualized within a coordinate system with separate axes for timeline, enterprise competencies, and qualitative characteristics. It is shown that the combination of differences in such indicators across various axes determines different trajectories of enterprise development. A symbolic framework is developed for formalizing an enterprise development scenario using the relationship of differences across specific coordinates representing the progress of enterprise development. It is argued that enterprise development should only be tracked if its duration exceeds a certain minimum time threshold. The larger the enterprise, the longer this minimum time required to identify its development. General positive and neutral formal scenarios of enterprise development are identified, along with their characteristics under different conditions of the relationship between differences in specific coordinates representing the progress of enterprise development, which have a positive qualitative assessment. General negative and conditionally negative formal scenarios of enterprise development are also identified, with their characteristics outlined based on different conditions of the relationship between differences in specific coordinates representing the progress of enterprise development, which have a negative qualitative assessment.